Renoprotective Effects of AVE0991, a Nonpeptide Mas Receptor Agonist, in Experimental Acute Renal Injury. (29th January 2012) - Barroso, Lívia Corrêa; Silveira, Kátia Daniela; Lima, Cristiano Xavier; Borges, Valdinéria; Bader, Michael; Rachid, Milene; Santos, Robson Augusto Souza; Souza, Danielle Gloria; Simões e Silva, Ana Cristina; Teixeira, Mauro Martins
Abstract : Renal ischemia and reperfusion (I/R) is the major cause of acute kidney injury in hospitalized patients. Mechanisms underlying reperfusion-associated injury include recruitment and activation of leukocytes and release of inflammatory mediators. In this study, we investigated the renal effects of acute administration of AVE0991, an agonist of Mas, the angiotensin-(1–7) receptor, the angiotensin-(1–7) receptor, in a murine model of renal I/R. Male C57BL/6 wild-type or Mas −/− mice were subjected to 30 min of bilateral ischemia and 24 h of reperfusion. Administration of AVE0991 promoted renoprotective effects, as seen by improvement of function, decreased tissue injury, prevention of local and remote leucocyte infiltration, and release of the chemokine, CXCL1. I/R injury was similar in WT and Mas −/− mice, suggesting that endogenous activation of this receptor does not control renal damage under baseline conditions. In conclusion, pharmacological interventions using Mas receptor agonists may represent a therapeutic opportunity for the treatment of renal I/R injury.